UJI APLIKASI ALAT BANTU DAN PENGERING SEDERHANA DALAM INDUSTRI PENGOLAHAN EMPING MELINJO SKALA RUMAH TANGGA - , Yuniarti; Zubaidi, Thohir; Santoso, Pudji (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2005)
Emping melinjo agroindustry is one of the agribusiness activity which can gives big job opportunity for thewomen. Nevertheless, during doing their work, the women donât care about their body position, so that there is noworking pleasure and they feel quick tired. Increasing their working pleasure can be done by using right supportingtools that can results the right body position. The main problem faced by the female labour in emping melinjoagroindustry during rainy season is lack of sunlight, consequently quality of the produce will drop sharply. The aimsof this assessment were 1) to determine supporting tools which can increase working pleasure of the female labour,and 2) to test the use of simple drier for increasing drying process efficiency in emping melinjo agroindustry duringrainy season. This assessment had been done in Tanggung and Siraman village, Blitar, from January 2001 toDecember 2001. In this assessment, the modified (introduction) supporting tools were tested by the female labour formaking emping melinjo, then the produces were compared to those using old supporting tools. Introductionsupporting tools which tested were wooden and stone hitting layer, suitable wooden chair, stone-hammer and ironhammer.Drier which tested was simple drier using kerosene as fuel source with low electrical energy. The parameterswhich observed were labour productivity, working pleasure and product quality. The result showed, that the rightsupporting tools which recommended to get working pleasure for female labour in emping melinjo agroindustry werestone hitting layer as high as 30 cm, wooden chair as high as 30 cm and wooden hammer with cylindrical iron at theirtip. These supporting tools resulted same productivity and working pleasure with those old supporting tools, althoughthese introduction tools were new for the female labour. The use of simple drier can saved time and place needed fordrying process of emping melinjo compared to those using sunlight. The use of this simple drier was recommended inrainy season because it can assured the continuity of production and increasing the absorption of working labour andincreasing the labour income.Key words : gnetum geremons, agroindustry, female labour, drier, BlttarAgroindustri emping melinjo merupakan salah satu kegiatan agribisnis yang memberi kesempatan kerja yangluas bagi wanita. Namun demikian, dalam melaksanakan pekerjaannya wanita cenderung tidak mempedulikan posisiatau caranya bekerja, sehingga tidak terasa adanya kenyamanan bekerja. Peningkatan kenyamanan bekerja tenagawanita dapat dilakukan dengan penggunaan alat bantu yang tepat sehingga posisi tubuh benar. Masalah utama yangdihadapi perajin emping melinjo pada waktu musim penghujan adalah kurangnya sinar matahari, sehinggapengeringan tidak dapat dilakukan secara optimal. Pengkajian ini dilakukan dengan tujuan 1) menentukan alat bantuyang dapat meningkatkan kenyamanan bekerja tenaga wanita, dan 2) menguji penggunaan alat pengering sederhanauntuk meningkatkan efisiensi proses pengeringan dalam pengolahan emping melinjo selama musim penghujan.Pengkajian dilakukan di Desa Tanggung dan Siraman, Blitar dari bulan Januari 2001 sampai dengan Desember 2001.Dalam pengkajian ini alat bantu yang telah dimodifikasi (alat bantu introduksi) diuji oleh tenaga kerja wanita untukmengolah emping melinjo, kemudian hasilnya dibandingkan dengan hasil dari penggunaan alat bantu semula. Alatbantu introduksi yang akan dicoba adalah alat bantu alas pemipih emping melinjo dari kayu dan batu, alas duduk darikayu serta pemipih emping melinjo dari batu dan palu besi. Alat pengering yang diuji adalah alat pengering sederhanaberbahan bakar minyak tanah dan berdaya listrik rendah. Parameter yang diamati meliputi produktivitas tenaga kerjawanita, kenyamanan bekerja tenaga wanita serta mutu hasil olah. Hasil pengkajian menunjukkan, bahwa alat bantu138Jurnal Pengkajian dan Pengembangan Teknologi Pertanian Vol. 8, No.1, Maret 2005 : 137-149yang tepat dan dapat dianjurkan untuk mendapatkan kenyamanan bekerja bagi tenaga wanita dalam pengolahanemping melinjo adalah alat bantu berupa alas duduk setinggi 30 cm, pemipih melinjo dari palu kayu berujung besisilinder dan alas pemipih dari batu setinggi 30 cm. Alat pengering sederhana yang digunakan dapat menghemat waktudan tempat dalam pengolahan emping melinjo dibandingkan dengan penggunaan sinar matahari. Penggunaan alatpengering sederhana dianjurkan untuk musim penghujan karena dapat menjamin kontinuitas produksi danmeningkatkan penyerapan tenaga kerja serta keuntungan perajin.Kata kunci: emping melinjo, agroindustri, tenaga kerja wanita, alat pengering, Blitar